2020
DOI: 10.1002/anie.202004501
|View full text |Cite
|
Sign up to set email alerts
|

Stable Actinide π Complexes of a Neutral 1,4‐Diborabenzene

Abstract: The π coordination of arene and anionic heteroarene ligands is a ubiquitous bonding motif in the organometallic chemistry of d‐block and f‐block elements. By contrast, related π interactions of neutral heteroarenes including neutral bora‐π‐aromatics are less prevalent particularly for the f‐block, due to less effective metal‐to‐ligand backbonding. In fact, π complexes with neutral heteroarene ligands are essentially unknown for the actinides. We have now overcome these limitations by exploiting the exceptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 160 publications
0
16
0
4
Order By: Relevance
“…The U1-(h 4 -C anth ) distances narrowly range from 2.638(5) to 2.676(6) A. Tetrahapto coordination of aromatic or carbocyclic ligands to the actinides is rare, but a handful of terminal cyclobutadienide complexes are known. [68][69][70][71] The U1-(h 4 -C anth ) distances in 1 18C6 $4THF are signicantly longer than the uranium-cyclobutadienide distances found in [Na ( 31 where the elongation of the thorium-arenide distances as compared to 1 18C6 $4THF possibly result from the slight size difference in the ionic radii between thorium and uranium (e.g., Th(IV), C.N. ¼ 6, r ¼ 0.94 A vs. U(IV), C.N.…”
Section: Synthesismentioning
confidence: 94%
See 1 more Smart Citation
“…The U1-(h 4 -C anth ) distances narrowly range from 2.638(5) to 2.676(6) A. Tetrahapto coordination of aromatic or carbocyclic ligands to the actinides is rare, but a handful of terminal cyclobutadienide complexes are known. [68][69][70][71] The U1-(h 4 -C anth ) distances in 1 18C6 $4THF are signicantly longer than the uranium-cyclobutadienide distances found in [Na ( 31 where the elongation of the thorium-arenide distances as compared to 1 18C6 $4THF possibly result from the slight size difference in the ionic radii between thorium and uranium (e.g., Th(IV), C.N. ¼ 6, r ¼ 0.94 A vs. U(IV), C.N.…”
Section: Synthesismentioning
confidence: 94%
“…In this case, the dbb-An bond was found to be strong, though, also primarily electrostatic in character. 31 In specic regards to thorium, Gambarotta and co-workers have reported the synthesis of the thorium naphthalenide complexes The latter is the only reported actinide-arenide sandwich complex; however, low yields and persistent impurities prevented characterization beyond the determination of its solidstate molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Harmansr elated NHC-stabilized derivative V (NHC = N-heterocyclic carbene,F igure 1) showed closedshell character, [19] which suggested that further fine-tuning of the acenes electronics is required to eventually prompt biradical formation, and to stabilize the resulting open-shell configuration. Due to their unique s donor and p acceptor capabilities,c AACs are powerful Lewis bases, [20] which have already proven their efficiencyinboron chemistry to support realization of uncommon and highly reactive,n eutral molecules [21] and radical species. [22] Fori nstance,d iborenes of the type (L)(ER)B = B(ER)(L) (ER = SBu, SPh, SePh) feature ac losed-shell ground state for L = NHC,w hile at riplet ground state was found for L = cAAC; both compounds show distinct differences in their geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the dbb-An bond was found to be very strong, though, also primarily electrostatic in character. 29 In specific regards to thorium, Gambarotta and co-workers have reported the synthesis of the thorium naphthalene complexes 31 The latter is the only reported actinide-arene sandwich complex; however, low yields and persistent impurities prevented characterization beyond the determination of its solid-state molecular structure.…”
Section: Introductionmentioning
confidence: 99%